Utilização de processos biológicos e oxidativos avançados no tratamento dos antibióticos norfloxacino e sulfato de gentamicina presentes em meio aquoso - Lucilaine Valeria de Souza Santos (2014)
In the recent years the scientific community has shown great interest in the so-called "emerging pollutants", which include different classes of substances - endocrine disruptors, pharmaceuticals, drugs of abuse, preservatives, among other compounds - and their metabolites or degradation products. Recent advances in analytical detection of these compounds conclude that they are not effectively removed in sewage treatment plants (STPs) when using traditional treatment. This work presents a study of the behavior of antibiotics norfloxacin and gentamicin sulfate, facing advanced biological and oxidation treatment systems, as well as the toxicity assessment of the solutions engendered after each treatment and the identification of metabolites/degradation products generated. It investigates, likewise, aerobic and anaerobic biodegradability, using different biomasses, with and without acclimatization. It was observed that norfloxacin is not removed even after the biologically acclimatization of the biomass. Gentamicin sulfate exhibited values of up to 96% degradation using anaerobic treatment. . In studies involving oxidation processes and advanced oxidation processes were used UV, H2O2, UV/H2O2, Fenton and Photo-Fenton. The tests involving the oxidation of Fenton and photo-Fenton were the ones with the best results, both degradation and mineralization for both antibiotics. With the use of norfloxacin were obtained 87 and 99,7% of degradation by using Fenton oxidation and photo-Fenton, respectively. Otherwise, with the use of gentamicin were observed degradation of 99% in the two trials. Besides biodegradability tests and advanced oxidative, this work presents a study of possible metabolites generated through biotransformation performed by the human body. To this end, were used metalloporphyrin compounds that are capable of mimicking the reactions mediated by cytochrome P450. It was observed that the solutions analyzed after metalloporphyrins assays were more toxic than the initials ones. These results suggest that metabolites formed or synergism are able to confer toxicity to the solutions. One must note that similar processes may occur during excretion of these drugs.